The relationship between the changes in inflammatory parameters and response to treatment in major depression patients starting antidepressant treatment - Abdullah Burak Uygur; Şeyda Çankaya (Acta Medica Alanya)
Aim: Changes in inflammatory parameters such as cytokines, stress hormones and C reactive protein that occur in depression, are important in understanding the pathophysiology of depression and developing new treatment approaches. The main purpose of this study was to determine the changes in inflammatory markers in patients with major depression, before and after antidepressant treatment, as well as to determine the effect of antidepressant treatment types on these changes.Methods: This study was a single center, retrospective study. According to the retrospective records of the last five years in the psychiatry outpatient clinic of Alanya Alaaddin Keykubat University Training and Research Hospital, the patients diagnosed with Major Depressive Disorder (MDD), started on single antidepressant treatment for the first time and who used antidepressant treatment for at least 6-8 weeks, were included in the study. Patients whose Hamilton Depression Rating Scale (HDRS), complete blood count, C reactive protein and cortisol values were reached from the system during MDD treatment, constituted the sample of the study.Results: In the present study, after the antidepressant treatment, while HDRS scores decreased significantly in patients with Major Depression compared to before treatment (p<0,001), no significant correlation was found between the changes in inflammatory parameters and the response to treatment (p>0,05). This condition was independent of the type of antidepressant used in the treatment (p>0,05 in the SSRI treatment group, p>0,05 in the SNRI treatment group). In addition, it was observed that the decrease in depression scores was not associated with the type of antidepressant (p=0,001, in the SSRI treatment group, p=0,005, in the SNRI treatment group).Conclusion: Results to support the inflammatory hypothesis in Major Depressive Disorder were not conclusive in this study. Considering that the pathophysiology of depression is quite complex, it could be argued that a single group of blood tests may not be sufficient to explain the link between inflammation and depression. Considering all the limitations of the study, a future a prospective study to prove the inflammatory hypothesis in MDD, including the detailed blood, BOS tests, along with more comprehensive neuroimaging parameters on the brain pathways, might provide more effective results.